Social norms in medieval Scandinavia - Morawiec, Jakub; Jochymek, Aleksandra, 1991-; Bartusik, Grzegorz, 1990- (Beyond medieval Europe., 2019)
In the Viking Age and medieval Scandinavia, social values such as reputation, honour, and friendship, were integral to the development of rituals, customs, religion, literature, and language. Everyday norms are mainly conveyed orally or ritually, and rarely in a written or material shape. Despite this, the Old Norse-Icelandic literary corpus remains the most important source of our present-day knowledge of social development in the medieval North. New research methods allow us to explore how relics of the material culture of the medieval north can confront, corroborate, or disprove the depiction of social norms in medieval Scandinavian literature. This volume considers in depth how social norms affected the creation and functioning of societies in the medieval North, approaching the topic from a range of disciplinary angles including law-making, politics, religion, and literacy